Surface-modified high-nickel ternary positive electrode material as well as preparation method and application thereof
By doping tellurium elements on the surface of high-nickel ternary positive electrode materials, the problem of poor circulation and rate performance of existing nickel-rich ternary positive electrode materials is solved, and higher battery rate performance and cycle capabilities are achieved.
Patent Information
- Application Number
- CN202411439833.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-15
- Publication Date
- 2025-02-11
AI Technical Summary
The current nickel-rich ternary cathode materials have poor circulation and rate performance, mainly due to structural damage and side reactions caused by cationic mixed discharge and Ni3+ oxidation to Ni4+.
By doping tellurium on the surface of the high-nickel ternary positive electrode material, a high-nickel ternary positive electrode material with surface doping tellurium is formed, and the strong combination of Te and oxygen is used to generate TM-O plate bonding to prevent the precipitation of surface oxygen and reduce the reduction of the Structural degradation.
It improves the rate performance and circulation ability of the buckle battery, enhances the structural stability of the positive electrode material, suppresses side reactions, and improves electrochemical performance.
Smart Images

Figure CN119419260A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of ternary lithium battery materials, and in particular relates to a surface-modified high-nickel ternary positive electrode material and a preparation method and application thereof. Background Art
[0002] Since their first commercialization in the 1990s, lithium-ion batteries have been widely used in portable electronic devices such as drones, mobile phones and laptops. Currently, lithium-ion batteries have been widely used in the field of electric vehicles. Lithium-ion batteries are composed of four main components: positive electrode, negative electrode, separator and electrolyte. Among these components, the positive electrode material largely controls the operating voltage and storage capacity. At the same time, the positive electrode is mostly made of rare metals, which accounts for about 22.4% of the total battery cost. Therefore, the development of high-performance, low-cost positive electrodes is a necessary condition for reducing the cost of lithium-ion batteries.
[0003] Cathode materials such as lithium cobalt oxide (LCO), lithium iron phosphate (LFP), lithium titanate (LTO), lithium manganese oxide (LMO), lithium nickel cobalt aluminum oxide (NCA) and lithium nickel manganese cobalt oxide (NCM) have been widely studied. Among them, NCM has the best overall performance and is becoming increasingly popular in the global lithium-ion battery market. Nickel-rich ternary cathode materials (LiNi x Co y Mn z O2, x≥0.8,x+y+z=1) has a series of advantages over traditional medium- and low-nickel ternary cathode materials, including: (1) The price of nickel is lower than that of cobalt. (2) Higher specific capacity (170-200mAh / g); for example, the specific capacity of NCM811 is about 200 mAh / g, while the specific capacity of lithium cobalt oxide (LiCoO2) cathode materials is about 140-170 mAh / g. (3) Working voltage 3.6 ~ 4.2 V. For example, the working voltage of NCM811 is about 3.8 V, while the working voltage of LiCoO2 cathode materials is about 3.0-3.8 V. (4) Higher theoretical energy density, which means that nickel-rich ternary cathode materials have the potential to store more energy per unit weight or unit volume.
[0004] However, the poor cycle performance and rate performance of nickel-rich ternary cathode materials are the biggest obstacles to their commercialization. The main reasons are the mixed discharge of cations and the Ni 3+ Oxidized to Ni 4+ , which may lead to side reactions with the electrolyte to form Ni-O impurity phases, causing irreversible damage to the layered structure of NCM and affecting the Li + Therefore, it is necessary to develop a nickel-rich ternary cathode material with higher cycle performance and rate performance. Summary of the invention
[0005] In order to overcome the above-mentioned defects of the prior art, the purpose of the present invention is to provide a surface-modified high-nickel ternary positive electrode material and a preparation method and application thereof, so as to solve the technical problems of poor cycle performance and rate performance of existing nickel-rich ternary positive electrode materials.
[0006] To achieve the above object, the present invention is implemented through the following technical solutions: In a first aspect, the present invention provides a surface-modified high-nickel ternary positive electrode material, wherein the surface-modified high-nickel ternary positive electrode material is a high-nickel ternary positive electrode material doped with tellurium elements on the surface, wherein the chemical formula of the high-nickel ternary positive electrode material is LiNi x Co y Mn z O2, x≥0.8, y>0, x+y+z=1, the mass fraction of tellurium doping is 0.5%~1.0%.
[0007] In a second aspect, the present invention provides a method for preparing a surface-modified high-nickel ternary positive electrode material as described in the first aspect, comprising the following steps: (1) mixing a tellurium source with a nickel-cobalt-manganese ternary precursor, heating and stirring, and obtaining a nickel-cobalt-manganese ternary precursor with a tellurium element doped on the surface; (2) mixing a nickel-cobalt-manganese ternary precursor doped with tellurium on its surface with a lithium source to obtain a mixed material; (3) The mixture is sintered in an oxidizing atmosphere to obtain a high-nickel ternary positive electrode material with tellurium element doped on the surface.
[0008] Preferably, in step (1), the heating and stirring temperature is 50-60° C., and the stirring time is 6-8 h.
[0009] Preferably, the tellurium source is one or more of telluric acid, tellurite, tellurate, tellurite, hydrogen tellurate, and hydrogen tellurite.
[0010] Preferably, the chemical formula of the nickel-cobalt-manganese ternary precursor is Ni x Co y Mn z (OH)2, in the formula, x≥0.8, y>0, x+y+z=1.
[0011] Preferably, the mass ratio of the tellurium source to the nickel-cobalt-manganese ternary precursor is (0.5-1.0):100.
[0012] Preferably, in step (2), the lithium source is one or more of lithium hydroxide, lithium carbonate, lithium fluoride, lithium chloride, and lithium nitrate; and the molar ratio of the total number of moles of metal elements in the nickel-cobalt-manganese ternary precursor to the lithium element in the lithium source is (0.4-0.6):1.
[0013] Preferably, in step (3), the sintering conditions are: firstly heating the temperature to 700-770°C at a heating rate of 4-5°C / min, and then sintering at a constant temperature of 700-770°C for 10-15 h.
[0014] In a third aspect, the present invention provides a positive electrode plate, which includes the surface-modified high-nickel ternary positive electrode material described in the first aspect.
[0015] In a fourth aspect, the present invention provides a lithium-ion battery, comprising the positive electrode sheet described in the third aspect.
[0016] The beneficial effects of the present invention are: The present invention provides a nickel-rich ternary positive electrode material doped with tellurium (Te) for surface modification. By doping the element Te on the surface of the nickel-rich ternary positive electrode material, Te and oxygen are strongly combined on the surface of the positive electrode material to generate TM-O plate bonding, thereby preventing the precipitation of surface oxygen, thereby reducing structural degradation and improving the rate performance and cycle capacity of button batteries. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] In order to more clearly illustrate the technical solution of the embodiment of the present invention, the drawings of the embodiment are briefly introduced below.
[0018] Figure 1 is a SEM image of the surface-modified high-nickel ternary positive electrode material prepared in Example 1; Figure 2 is a SEM image of the surface-modified high-nickel ternary positive electrode material prepared in Example 2; Figure 3 This is a SEM image of the high-nickel ternary positive electrode material prepared in Comparative Example 1; Figure 4 The curves of the discharge capacity of the high nickel ternary positive electrode materials prepared in Examples 1-2 and Comparative Example 1 as a function of the number of cycles are shown; Figure 5 The coulombic efficiency of the high nickel ternary positive electrode material prepared in Examples 1-2 and Comparative Example 1 varies with the number of cycles; Figure 6 It is the discharge capacity of the high nickel ternary positive electrode material prepared in Examples 1-2 and Comparative Example 1 at different rates. DETAILED DESCRIPTION
[0019] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0020] In a first aspect, an embodiment of the present invention provides a surface-modified high-nickel ternary positive electrode material, wherein the surface-modified high-nickel ternary positive electrode material is a high-nickel ternary positive electrode material with a tellurium element doped on the surface, wherein the chemical formula of the high-nickel ternary positive electrode material is LiNi x Co y Mn z O2, x≥0.8, y>0, x+y+z=1, the mass fraction of tellurium doping is 0.5%~1.0%.
[0021] The tellurium doping of the present invention is surface doping. Compared with bulk doping, surface doping mainly changes the electronic structure and chemical properties of the surface of the positive electrode material. For example, surface doping can significantly affect the surface conductivity, catalytic activity or friction performance of the material. In the present invention, enriching Te ions on the surface of the positive electrode material can convert Ni 3+ Converted to Ni 2+ , and accelerate the mixing of cations, which makes more ionic radius with Li + Similar to Ni 2+ The existence of 2+ Move into the Li plate, promoting the formation of surface rock salt phase, and the appropriate amount of rock salt phase will not only enhance the stability of the structure, but also inhibit side reactions and improve the electrochemical performance; on the other hand, Li + The diffusion capacity is enhanced, improving the battery's charge and discharge capacity.
[0022] In a second aspect, an embodiment of the present invention provides a method for preparing a surface-modified high-nickel ternary positive electrode material, comprising the following steps: (1) A tellurium source and a nickel-cobalt-manganese ternary precursor are mixed in a mass ratio of (0.5-1.0):100, and stirred at 50-60°C for 6-8h to obtain a nickel-cobalt-manganese ternary precursor doped with tellurium element on the surface; wherein the tellurium source is one or more of telluric acid, tellurite, tellurite, hydrogen tellurate, and hydrogen tellurite; the chemical formula of the nickel-cobalt-manganese ternary precursor is Ni x Co y Mn z (OH)2, in the formula, x≥0.8, y>0, x+y+z=1.
[0023] (2) A nickel-cobalt-manganese ternary precursor doped with tellurium is mixed with a lithium source to obtain a mixture; wherein the lithium source is one or more of lithium hydroxide, lithium carbonate, lithium fluoride, lithium chloride, and lithium nitrate; and the molar ratio of the total number of moles of metal elements in the nickel-cobalt-manganese ternary precursor to the molar ratio of the lithium element in the lithium source is (0.4-0.6):1.
[0024] (3) The mixture is first heated to 700-770°C at a heating rate of 4-5°C / min in an oxidizing atmosphere, and then sintered at a constant temperature of 700-770°C for 10-15 h to obtain a high-nickel ternary positive electrode material with tellurium element doped on the surface.
[0025] Compared with stirring at room temperature, stirring at 50-60°C in step (1) can increase the solubility of the dopant and the dispersion of the precursor, increase the molecular movement speed and thermal energy of the solute in the mixed solvent, and at high temperature, the interaction between the modifier molecules and the raw material molecules is enhanced, and the fluidity is improved, so that the modifier can better penetrate into the raw material, thereby achieving uniform mixing. In addition, high temperature also helps to accelerate chemical reactions and increase the activity of the modifier, thereby achieving the desired modification effect.
[0026] Compared with the existing method of first calcining to obtain unmodified positive electrode material, then mixing the unmodified positive electrode material with a modifier, and then calcining for a second time to prepare a modified positive electrode material, the present invention first mixes the precursor with the modifier to prepare a modified precursor, and then mixes it with a lithium source to prepare a modified positive electrode material. Only one calcination is required, and the preparation steps are simpler and more energy-efficient.
[0027] In order to make the objectives, technical solutions and advantages of the present invention more clear, the embodiments of the present invention will be described in further detail below.
[0028] Example 1 A surface modified high nickel ternary positive electrode material, the preparation method is as follows: (1) Preparation of nickel-cobalt-manganese ternary precursor According to the Ni∶Co∶Mn (molar ratio) = 8:1:1, NiSO4·H2O, CoSO4·6H2O and MnSO4·H2O were weighed and dissolved in an appropriate amount of deionized water to make the salt concentration in the solution 2mol / L. Sodium hydroxide (NaOH) solution and ammonia water (NH3·H2O) were added to the solution at the same time to control the pH of the solution to 11.0, and then the solution was stirred at a constant temperature of 50°C in a water bath, and the stirring speed was controlled to 500rpm and kept constant for 8 hours. After stirring, the mixture was filtered, the filter cake was repeatedly rinsed with deionized water for 3-5 times, and then dried in a 100°C oven for 12 hours to obtain the nickel-cobalt-manganese ternary precursor Ni 0.8 Co 0.1 Mn 0.1 (OH)2.
[0029] (2) Preparation of Te-modified Ni-Co-Mn ternary precursor H6TeO6 and the nickel-cobalt-manganese ternary precursor prepared in step (1) were dissolved in deionized water, wherein the mass ratio of H6TeO6 to the nickel-cobalt-manganese precursor was 1:100, and then stirred at a constant temperature of 50°C for 8 hours, filtered and dehydrated, and dried at 80°C overnight to remove excess water to obtain a Te-modified nickel-cobalt-manganese ternary precursor, recorded as 1% Te-NCM811.
[0030] (3) Preparation of Te surface modified high nickel ternary cathode materials Raw material mixing: grind the Te-modified nickel-cobalt-manganese ternary precursor obtained in step (2), and then put it into a high-efficiency mixer with lithium hydroxide to fully mix it to obtain a blended powder. The ratio of the molar amount of lithium element in lithium hydroxide to the total molar amount of nickel, cobalt and manganese in the Te-modified nickel-cobalt-manganese ternary precursor is 1:0.4; the mixer speed is 500 rpm, and the mixing time is 50 minutes.
[0031] High temperature sintering: The obtained blended powder is placed in an atmosphere furnace and heated to 770°C at a heating rate of 5°C / min, and then kept at 770°C for 10 h. The entire calcination process is carried out in a flowing oxygen atmosphere. After calcination and cooling, Te surface-modified lithium nickel cobalt manganese oxide positive electrode material is obtained.
[0032] Crushing and screening: The Te surface modified positive electrode material is placed in a high-speed crusher for crushing, and after crushing, it is passed through a 400-mesh sieve to obtain the positive electrode material crushed material.
[0033] Washing and drying: Add the positive electrode material crushed material into a container, add a certain amount of pure water (conductivity ≤ 2μs / cm), and make the water-to-material mass ratio 0.5:1. Stir at 400rpm for 5 min at room temperature, then filter and place the filter residue in a vacuum drying oven at 120℃ for 6-8 h, and obtain Te surface modified high nickel ternary positive electrode material after cooling.
[0034] Example 2 The only difference from Example 1 is that in step (2), the mass ratio of H6TeO6 to the nickel-cobalt-manganese precursor is 0.5:100, and a Te-modified nickel-cobalt-manganese ternary precursor is obtained, which is recorded as 0.5% Te-NCM811.
[0035] Example 3 The only difference from Example 1 is that in step (2), the mass ratio of H6TeO6 to the nickel-cobalt-manganese precursor is 0.6:100, and a Te-modified nickel-cobalt-manganese ternary precursor is obtained, which is recorded as 0.6% Te-NCM811.
[0036] Example 4 The only difference from Example 1 is that in step (2), the mass ratio of H6TeO6 to the nickel-cobalt-manganese precursor is 0.8:100, and a Te-modified nickel-cobalt-manganese ternary precursor is obtained, which is recorded as 0.8% Te-NCM811.
[0037] Comparative Example 1 The only difference from Example 1 is that the surface of the high nickel ternary positive electrode material prepared in Comparative Example 1 is not modified by Te. The specific steps are: A surface modified high nickel ternary positive electrode material, the preparation method is as follows: (1) Preparation of nickel-cobalt-manganese ternary precursor According to the Ni∶Co∶Mn (molar ratio) = 8:1:1, NiSO4·H2O, CoSO4·6H2O and MnSO4·H2O were weighed and dissolved in an appropriate amount of deionized water to make the salt concentration in the solution 2mol / L. Sodium hydroxide (NaOH) solution and ammonia water (NH3·H2O) were added to the solution at the same time to control the pH of the solution to 11.0, and then the solution was stirred at a constant temperature of 50°C in a water bath, and the stirring speed was controlled to 500rpm and kept constant for 8 hours. After stirring, the mixture was filtered, the filter cake was repeatedly rinsed with deionized water for 3-5 times, and then dried in a 100°C oven for 12 hours to obtain the nickel-cobalt-manganese ternary precursor Ni 0.8 Co 0.1 Mn 0.1 (OH)2.
[0038] (2) Preparation of high nickel ternary cathode materials Raw material mixing: grind the nickel-cobalt-manganese ternary precursor obtained in step (1), and then put it into a high-efficiency mixer with lithium hydroxide for thorough mixing to obtain a blended powder. The ratio of the molar amount of lithium element in lithium hydroxide to the total molar amount of nickel, cobalt and manganese in the nickel-cobalt-manganese ternary precursor is 1:0.4; the mixer speed is 500 rpm, and the mixing time is 50 min.
[0039] High temperature sintering: The obtained blended powder is placed in an atmosphere furnace and heated to 770°C at a heating rate of 5°C / min, and then kept at 770°C for 10 h. The entire calcination process is carried out in a flowing oxygen atmosphere. After calcination and cooling, Te surface-modified lithium nickel cobalt manganese oxide positive electrode material is obtained.
[0040] Crushing and screening: The positive electrode material of nickel cobalt manganese oxide is put into a high-speed crusher for crushing, and after crushing, it is passed through a 400-mesh sieve to obtain the positive electrode material crushed material.
[0041] Washing and drying: Add the positive electrode material crushed material into a container, add a certain amount of pure water (conductivity ≤ 2μs / cm), and make the water-to-material mass ratio 0.5:1. Stir at 400rpm for 5 min at room temperature, then filter and place the filter residue in a vacuum drying oven at 120℃ for 6-8 h. After cooling, a high-nickel ternary positive electrode material is obtained, which is recorded as NCM811.
[0042] Material Characterization and Performance Testing The surface morphology of Example 1, Example 2 and Comparative Example 1 was observed by scanning electron microscopy; button cells were assembled in a glove box filled with argon using a positive electrode sheet, a lithium metal sheet (negative electrode sheet) and an electrolyte. The cycle performance and rate performance of the button cell were tested on a battery testing system. The preparation method of the positive electrode sheet is as follows: first, 80% of the positive electrode material, 10% of acetylene black (conductive agent) and 10% of polyvinylidene fluoride (PVDF) (binder) were fully mixed and stirred for 4 h, and the obtained slurry was evenly coated on aluminum foil, dried in a vacuum oven at 120°C for 12 h, and then the aluminum foil after the slurry was dried was punched into a disc with a diameter of 12 mm. The electrolyte used 1 mol / L lithium hexafluorophosphate (LiPF6) dissolved in a mixture of ethyl carbonate (EC) and dimethyl carbonate (DMC) (EC:DMC = 1:1 volume ratio), and all electrochemical measurements were performed at room temperature. The performance (0.2C) of the button cells prepared in Examples 1-2 and Comparative Example 1 are shown in Table 1.
[0043] Table 1
[0044] Note: The above data are the average values of 3 sets of parallel samples, with a charge and discharge rate of 0.2C.
[0045] from Figures 1 to 3 It can be seen that the high-nickel ternary positive electrode materials with surface doped with tellurium elements prepared in Examples 1 to 2 of the present application are uniformly dispersed spherical particles. Compared with the positive electrode materials not doped with tellurium elements, the particle surfaces are smoother and show good surface morphology.
[0046] From Table 1 and Figures 4 and 5 It can be seen that compared with the positive electrode material without tellurium doping in Comparative Example 1, the high-nickel ternary positive electrode material with tellurium doped on the surface prepared in the present application has higher charge and discharge capacity, charge and discharge efficiency and better cycle stability.
[0047] It should be noted that the above embodiments all belong to the same inventive concept, and the description of each embodiment has its own focus. For matters that are not described in detail in some embodiments, reference may be made to the description in other embodiments.
[0048] The above-mentioned embodiments only express the implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. A surface-modified high-nickel ternary cathode material, characterized in that: The surface modified high nickel ternary positive electrode material is a high nickel ternary positive electrode material doped with tellurium on the surface, wherein the chemical formula of the high nickel ternary positive electrode material is LiNi x Co y Mn z O2, x≥0.8, y>0, x+y+z=1, and the mass fraction of the tellurium element doping is 0.5%~1.0%.
2. A method for preparing the surface-modified high-nickel ternary positive electrode material according to claim 1, characterized in that: The following steps are involved: (1) mixing a tellurium source with a nickel-cobalt-manganese ternary precursor, heating and stirring, and obtaining a nickel-cobalt-manganese ternary precursor with a tellurium element doped on the surface; (2) mixing the nickel-cobalt-manganese ternary precursor doped with tellurium element on the surface with a lithium source to obtain a mixed material; (3) Sintering the mixture in an oxidizing atmosphere to obtain a surface-modified high-nickel ternary positive electrode material.
3. The method for preparing the surface-modified high-nickel ternary positive electrode material according to claim 2, characterized in that: In step (1), the heating and stirring temperature is 50-60° C., and the stirring time is 6-8 h.
4. The method for preparing the surface-modified high-nickel ternary positive electrode material according to claim 2, characterized in that: The tellurium source is one or more of telluric acid, tellurite, tellurate, tellurite, hydrogen tellurate, and hydrogen tellurite.
5. The method for preparing the surface-modified high-nickel ternary positive electrode material according to claim 2, characterized in that: The chemical formula of the nickel-cobalt-manganese ternary precursor is Ni x Co y Mn z (OH)2, in the formula, x≥0.8, y>0, x+y+z=1.
6. The method for preparing the surface-modified high-nickel ternary positive electrode material according to claim 2, characterized in that: The mass ratio of the tellurium source to the nickel-cobalt-manganese ternary precursor is (0.5-1.0):
100.
7. The method for preparing the surface-modified high-nickel ternary positive electrode material according to claim 2, characterized in that: In step (2), the lithium source is one or more of lithium hydroxide, lithium carbonate, lithium fluoride, lithium chloride, and lithium nitrate; and the molar ratio of the total molar number of metal elements in the nickel-cobalt-manganese ternary precursor to the lithium element in the lithium source is (0.4-0.6):
1.
8. The method for preparing the surface-modified high-nickel ternary positive electrode material according to claim 2, characterized in that: In step (3), the sintering conditions are: firstly heating the temperature to 700-770°C at a heating rate of 4-5°C / min, and then sintering at a constant temperature of 700-770°C for 10-15 h.
9. A positive electrode sheet, characterized in that: It includes the surface-modified high-nickel ternary positive electrode material as described in claim 1.
10. A lithium ion battery, characterized in that: Comprising the positive electrode sheet as described in claim 9.